Moisture, Fat and Fatty Acid Profile of Beef Dendeng in Malang City - Siti Resita Dijayanti; Djalal Rosyidi; Herly Evanuarini (Faculty of Animal Science Universitas Brawijaya, 2021)
The objective of this study was to determine the chemical characteristics of sliced beef dendeng and ground beef dendeng circulating in Malang city, i.e., fat content, fatty acid profile, moisture content, water activity and total calories. The quantitative descriptive analysis was used as research design. The data obtained were analyzed statistically by using the calculation formula according to the method used. The sliced dendeng and ground dendeng circulating in Malang city was used as sample. Beef dendeng circulating in Malang city had a fat content of 3.43-6.77%, moisture content of 19.56-27.50%, water activity of 0.69-0.84, and total calories of 93.38-136.77 kcal. The sliced beef dendeng with the best chemical characteristics (closed to national standard) was tested for fatty acid profile analysis. About 37 fatty acids were identified, consisting of 19 saturated fatty acids and 18 unsaturated fatty acids. It was concluded that both types of beef dendeng circulating in Malang city had different fat content, fatty acid profile, moisture content, water activity and total calories. These differences were influenced by raw materials, spices and processing used.